2021
DOI: 10.3390/microorganisms9071542
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Spike Mutations, L452R, T478K, E484Q and P681R, in the Second Wave of COVID-19 in Maharashtra, India

Abstract: As the global severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic expands, genomic epidemiology and whole genome sequencing are being used to investigate its transmission and evolution. Against the backdrop of the global emergence of “variants of concern” (VOCs) during December 2020 and an upsurge in a state in the western part of India since January 2021, whole genome sequencing and analysis of spike protein mutations using sequence and structural approaches were undertaken to identify possi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
467
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 548 publications
(484 citation statements)
references
References 39 publications
10
467
1
6
Order By: Relevance
“…In support of our results, Cherian and colleagues reported that the L452R mutation, and E484Q, could reduce intramolecular and intermolecular interactions and disrupts an electrostatic bond with Lys31 of hACE2 [27]. A change from a hydrophobic leucine on the protein surface to arginine (L452R) also increases its interactions with water molecules that could further stabilize the protein.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In support of our results, Cherian and colleagues reported that the L452R mutation, and E484Q, could reduce intramolecular and intermolecular interactions and disrupts an electrostatic bond with Lys31 of hACE2 [27]. A change from a hydrophobic leucine on the protein surface to arginine (L452R) also increases its interactions with water molecules that could further stabilize the protein.…”
Section: Resultssupporting
confidence: 88%
“…Thus, conformational changes in the RBD, induced by the E484Q mutation, could impact the stability of the hACE2 binding surface. Furthermore, Glu484 is as an important antibody escape site of SARS-CoV-2 and mutations at this location could impact the binding and neutralization by antibodies [27]. Studies have also demonstrated that the E484Q mutation could reduce the neutralization by plasma and antibodies by 10-fold [28].…”
Section: Resultsmentioning
confidence: 99%
“…As of 10 August 2021, the Delta variant has been reported in 142 countries [1]. The characteristic mutations reported in the spike gene of the B.1.617 lineage are D111D, L452R, D614G, P618R, and ±E484Q [3]. These mutations suggest increased ACE2 binding, transmissibility, and escape of neutralization [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic mutations reported in the spike gene of the B.1.617 lineage are D111D, L452R, D614G, P618R, and ±E484Q [3]. These mutations suggest increased ACE2 binding, transmissibility, and escape of neutralization [3][4][5][6]. Available evidence suggests increased transmissibility, secondary attack rate, hospitalization risk, and immune escape by the Delta variant [1,7].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been shown that the L452R mutation leads to increased infectivity, though slightly lower than with the N501Y mutation, compared to historical lineages 9 . Moreover, the L452R and the T478K possibly increase ACE2 binding and the stabilization of the ACE2-RBD complex and the P681R, present in the furin cleavage site, could enhance the transmissibility of the virus by its action on the S1-S2 cleavage 10 . These mutations confer equally to the virus a resistance to neutralizing monoclonal antibodies by disrupting their binding ability to the RBD spike 10 and could play a role in vaccine escape, which could explain its worldwide predominance.…”
mentioning
confidence: 99%